Characterization of cognition in mild cognitive impairment with and without Parkinson's disease. (2020) - Auclair-Ouellet, N.; Mandl, S.; Kibreab, M.; Haffenden, A.; Hanganu, A.; Cheetham, J.; Kathol, I.; Sarna, J.; Martino, D.; Monchi, O.
Highlights: Screening tests can diagnose PD-MCI but do not give detailed cognitive profiles. Criteria based on a complete neuropsychological battery identify more PD patients with MCI. The overall cognitive profile is similar in PD-MCI and MCI. Neuropsychological batteries and definition of impairment cut-offs should be refined.